Influence of phosphorus and inoculation with Rhizobium and AM fungi on growth and dry matter yield of chickpea - Solaiman, ARM; Rabbani, MG; Hossain, D; Hossain, GMA; Alam, MS (Bangladesh Journal of Scientific Research, 2012)
No abstract available DOI: http://dx.doi.org/10.3329/bjsr.v25i1.13047 Bangladesh J. Sci. Res. 25(1): 23-32, 2012